2021
DOI: 10.1111/1750-3841.15823
|View full text |Cite
|
Sign up to set email alerts
|

The fermentation‐time dependent proteolysis profile and peptidomic analysis of fermented soybean curd

Abstract: The proteolysis and peptidomic profiles and potential bioactivities of fermented soybean curd (furu) during fermentation were studied. The degree of protein hydrolysis (DH) and peptide content significantly increased with fermentation time (p < 0.05), and reached the highest levels after ripening for 90 days. The variety and abundance of bioactive peptides in furu samples were fermentation-time dependent, and furu ripening for 30 and 90 days showed the highest similarity. An ACE-inhibitor and antioxidant pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…And there are differences in strains, L. plantarum A3 fermentation than L. rhamnosus ATCC7469 fermentation is more obvious. Wei et al ( 39 ) had similar research results to ours. The diversity and abundance of bioactive peptides increased significantly after fermentation of their furu samples, probably because most of the enzymes secreted during fermentation degraded the proteins to produce more bioactive peptides.…”
Section: Resultssupporting
confidence: 89%
“…And there are differences in strains, L. plantarum A3 fermentation than L. rhamnosus ATCC7469 fermentation is more obvious. Wei et al ( 39 ) had similar research results to ours. The diversity and abundance of bioactive peptides increased significantly after fermentation of their furu samples, probably because most of the enzymes secreted during fermentation degraded the proteins to produce more bioactive peptides.…”
Section: Resultssupporting
confidence: 89%
“…Due to the low sugar content and to promote microbial growth and activity, resultant dough was supplemented with 1% (w w −1 ) of glucose before fermenting with LAB and yeast starters. Proteolysis is fermentation‐time dependent and longer fermentation maximizes BPs release (Wei et al., 2021 ). Consequently, we monitored RLPI dough fermentation at 30°C for 8 days.…”
Section: Resultsmentioning
confidence: 99%
“…Wei et al. (2021) studied the proteolytic and peptidomic characteristics of fermented tofu during fermentation. Zhang et al.…”
Section: Resultsmentioning
confidence: 99%
“…Currently peptidomic analyses of protein hydrolysates have focused on the effect of fermentation and hydrolysis time on the peptidome. Wei et al (2021) studied the proteolytic and peptidomic characteristics of fermented tofu during fermentation. Zhang et al (2021) examined the peptidomic pattern of alcalase hydrolysates of Auxenochlorella pyrenoidosa protein and found that the enhanced antioxidant properties exhibited by longer hydrolysis times were attributed to the production of shorter peptides.…”
Section: Peptidomics Profilesmentioning
confidence: 99%